PELAKSANAAN DAKWAH MAJELIS AL-IHSAN DI LORONG BUKIT KELURAHAN PINTU PADANG II KECAMATAN BATANG ANGKOLA KABUPATEN TAPANULI SELATAN - Rizky Fauzi Hasibuan (ADISAM PUBLISHER, 2024)
In the implementation of da'wah, problems were encountered. This research was motivated by the problems of da'wah that occurred in one of the assemblies and also problems in the community in Pintu Padang II Village during the implementation of da'wah. The public's lack of interest in participating in the implementation of da'wah in the assembly, both in the da'wah events which are held regularly every week, as well as in every program carried out in the assembly. Judging from the decline in the number of members since its founding, the public is starting to become less enthusiastic about this assembly. The many issues circulating among the community, the many negative things related to the systematic implementation of da'wah carried out in this assembly have hampered the message of da'wah. The type of research used is field research with a descriptive qualitative approach. The data collection methods used were observation, interviews and documentation. The results of the research are the Implementation of the Al-Ihsan Assembly's Da'wah in Lorong Bukit, Pintu Padang II Village, Batang Angkola District, South Tapanuli Regency, which consists of, first: Implementation of the Al-Ihsan Assembly's Da'wah, where there are problems in this Assembly's preaching, namely the obligation to pay infaq and pay fees, and the existence of a caste system makes it difficult for people who come from the poor to have self-confidence when taking part in studies at this Assembly. Second: the problem of mad'u (Object of Da'wah), where there is the problem of mad'u who lack confidence in the program da'wah carried out in the da'wah activities carried out